CCAFS Climate-Smart Villages AR4D sites - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
This map illustrates the location of the Climate-Smart Villages AR4D sites facilitated by CCAFS across 20 focus countries. There are also partner-facilitated CSV sites, numbering in their hundreds, where partners bring together and replicate various climate-smart solutions.